(untitled) (Международный научный журнал «Инженер», 2026)
In this study, the possibilities of purification in natural conditions through streams without covering the contaminants contained in the drainage waters were studied. During the work, the impact of biological, physical and chemical processes occurring in open drainage channels on water quality indicators was analyzed. The results of the experiment showed that non-covering ditches interact with soil, microflora and plants, serving the natural purification of drainage waters. In particular, practical observations have revealed a significant reduction in organic matter, nitrogen and phosphorus compounds, suspension and other polluting components.The results of the study are important in the environmentally and economically efficient formation of drainage systems, in the Prevention of secondary pollution of water used in agriculture. At the same time, it is recommended to optimize, taking into account hydromorphological and environmental conditions, in order to enhance the natural cleaning process in non-coating ditches.